2015
DOI: 10.1002/lt.24070
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen years and 382 extended right grafts from in situ split livers in a multicenter study: Are these still extended criteria liver grafts?

Abstract: In situ split liver extended right grafts (SL-ERGs) are still considered marginal grafts. Our aim was to verify this statement at the present time. From 1997 to 2011, a multicenter, retrospective study based on a prospective database was performed at 9 liver transplantation (LT) centers in northern Italy; it included 382 in situ SL-ERG transplants in adults. There were 358 primary LTs and 24 retransplantations (RETXs). The 1-, 3-, and 5-year overall graft survival rate for LT with in situ SL-ERGs were 73.5%, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 22 publications
1
23
0
2
Order By: Relevance
“…Conversely, relatively sick recipients, such as those with high Model for End‐Stage Liver Disease (MELD) scores, ICU‐bound, and retransplant patients, received split grafts in this series, although the use of split grafts in critically‐ill recipients, such as those with a MELD score >30, and retransplant patients diminished the patient survival . A recent report of the large series of ERL grafts from the North Italy Transplant Program clearly showed that retransplantation was identified to be a significant prognostic factor influencing the graft survival, and therefore it suggested that ERL grafts should not be used for retransplant recipients . The three retransplant recipients receiving ERL grafts died in this series, although the poor results of split LT for these retransplant recipients may not only be related to the type of graft.…”
Section: Discussionmentioning
confidence: 94%
“…Conversely, relatively sick recipients, such as those with high Model for End‐Stage Liver Disease (MELD) scores, ICU‐bound, and retransplant patients, received split grafts in this series, although the use of split grafts in critically‐ill recipients, such as those with a MELD score >30, and retransplant patients diminished the patient survival . A recent report of the large series of ERL grafts from the North Italy Transplant Program clearly showed that retransplantation was identified to be a significant prognostic factor influencing the graft survival, and therefore it suggested that ERL grafts should not be used for retransplant recipients . The three retransplant recipients receiving ERL grafts died in this series, although the poor results of split LT for these retransplant recipients may not only be related to the type of graft.…”
Section: Discussionmentioning
confidence: 94%
“…However, when multiple risk factors are avoided (short ischemia time, non-urgent recipient status, young donor age, etc . ), the right trisegment graft can achieve excellent outcomes and is no longer considered to be marginal by experienced centers[26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…donor-to-recipient weight ratio, retransplantation, and UNOS I-IIA status. (4) Excellent SLT outcomes were reported thereafter in single-center series both for left grafts (3) and for ERGs (5) even using pediatric donors. (6) The national SLT policy (7) was further enhanced in 2015: all livers from deceased adult standard risk donors aged 50 years are now mandatorily evaluated for SLT, unless allocated to urgent patients; if SLT is performed, centers are free to allocate the ERG other than on the Model for End-Stage Liver Disease score.…”
mentioning
confidence: 91%